If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = x + -12 Reorder the terms: 11 = -12 + x Solving 11 = -12 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 11 + -1x = -12 + x + -1x Combine like terms: x + -1x = 0 11 + -1x = -12 + 0 11 + -1x = -12 Add '-11' to each side of the equation. 11 + -11 + -1x = -12 + -11 Combine like terms: 11 + -11 = 0 0 + -1x = -12 + -11 -1x = -12 + -11 Combine like terms: -12 + -11 = -23 -1x = -23 Divide each side by '-1'. x = 23 Simplifying x = 23
| 88+2x+62=2x+26 | | 4/(x-2)=6 | | 1.1x-3x=-34.3 | | 12-r=-8 | | 26=(5-x) | | -2(7u-2)+3u=1+2(2u-1) | | 40=2(x-4) | | -2=n+(-17) | | -5+.25c=15 | | 2x^2+3x+8=3x-10 | | 6x-1=133 | | v-(-10)=17 | | 20+8x-88=-12 | | 4s^3+12s^2-64s-192=0 | | 4(3x+10)=100 | | r^3-9r=8r^2 | | 8-m=3m+2 | | -126=b-118 | | -17b=170 | | a/bxb | | 6=(t-9)(t+11) | | 104=-26v | | 4(2a+b)-3(3a-4b)= | | 18+v=20 | | 7m/5=21 | | X/4x4 | | 5/4x-4=12 | | 7x=8x-10 | | (X+3)+3(x-1)=o | | 7m/5212 | | 9x+3y=(-6) | | -24=4(k+3) |